ANALISIS PERAN SIKAP LINGKUNGAN PADA PENGARUH INOVASI TERHADAP NIAT BELI PRODUK MAKANAN ALAMI - Much Yudi Firmansyah; Adenin Raditya Diandra; Mercylina Rifka Cisandra; Andy Yulianto; Nafisa Rafi Azumah; Syelbi Huriyah (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study analyzes the role of pro-environmental attitude in the influence of innovativeness on the purchase intention of natural food products. The research uses a quantitative approach. The population studied consists of the people of Sukoharjo, with a non-probability sampling technique and purposive sampling. The sample used consists of 200 respondents. The data used in this study is primary data, collected through the distribution of questionnaires. To analyze the data, this study employs the Partial Least Square (PLS) method with the assistance of SMARTPLS software.